Rút gọn P=\(\sqrt{2}\left(\sqrt{8}-2\sqrt{8}\right)+2\sqrt{6}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(=x^2+4\sqrt{3}x-4\sqrt{3}-1\)
\(=\left(x^2-1\right)+\left(4\sqrt{3}x-4\sqrt{3}\right)\)
\(=\left(x-1\right)\left(x+1\right)+4\sqrt{3}\left(x-1\right)\)
\(=\left(x-1\right)\left(x+1+4\sqrt{3}\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a, \(P=\left(\frac{\sqrt{x}-1}{3\sqrt{x}-1}-\frac{1}{3\sqrt{x}+1}+\frac{8\sqrt{x}}{9x-1}\right):\left(1-\frac{3\sqrt{x}-2}{3\sqrt{x}+1}\right)\)ĐK : \(x\ge0;x\ne\frac{1}{9}\)
\(=\left(\frac{\left(\sqrt{x}-1\right)\left(3\sqrt{x}+1\right)-3\sqrt{x}+1+8\sqrt{x}}{9x-1}\right):\left(\frac{3\sqrt{x}+1-3\sqrt{x}+2}{3\sqrt{x}+1}\right)\)
\(=\left(\frac{3x-2\sqrt{x}-1-3\sqrt{x}+1+8\sqrt{x}}{9x-1}\right):\frac{3}{3\sqrt{x}+1}\)
\(=\frac{3x+3\sqrt{x}}{9x-1}:\frac{3}{3\sqrt{x}+1}=\frac{3\sqrt{x}\left(\sqrt{x}+1\right)\left(3\sqrt{x}+1\right)}{3\left(9x-1\right)}\)
\(=\frac{\sqrt{x}\left(\sqrt{x}+1\right)}{3\sqrt{x}-1}\)
Ta có : \(\frac{x+\sqrt{x}}{3\sqrt{x}-1}=\frac{6}{5}\Rightarrow5x+5\sqrt{x}=18\sqrt{x}-6\)
\(\Leftrightarrow5x-13\sqrt{x}+6=0\Leftrightarrow x=\frac{9}{25};4\)( tmđk )
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(P=\sqrt{x}+\sqrt{y}
\)
\(\Rightarrow P.\sqrt{2}=\sqrt{2x}+\sqrt{2y}\)
\(\Rightarrow P\sqrt{2}=\sqrt{X\left(X+Y\right)}+\sqrt{\left(X+Y\right)Y}\)
\(\ge\sqrt{x.x}+\sqrt{y.y}=x+y=2\)
\(\Rightarrow Pmin=\frac{2}{\sqrt{2}}=\sqrt{2}\Leftrightarrow\orbr{\begin{cases}x=0,y=2\\y=0,x=2\end{cases}}\)
\(P=\sqrt{2}\left(\sqrt{8}-2\sqrt{8}\right)+2\sqrt{6}\)
\(=\sqrt{2}\left(2\sqrt{2}-4\sqrt{2}\right)+2\sqrt{6}\)
\(=4-8+2\sqrt{6}=-4+2\sqrt{6}\)